Intimate Cyber Connectivity within Matrimony: A Comparative Jurisprudential Analysis of Electronic Sexual Relations among Spouses - Mohammed, Hossameldeen Khalil Farag; Jindiya, Nur Ahmad (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
The profound enjoyment between spouses stands as a paramount objective of marriage, receiving explicit attention and delineation within Sharia law. In the contemporary era marked by a significant information revolution, novel forms of enjoyment, previously unknown, have surfaced, notably the practice of "electronic sex" between spouses. This research delves into the exploration of this topic, elucidating its various forms, types, motivating factors, justifications for its practitioners, and the associated risks. An examination of legal evidence related to electronic sex is undertaken to ascertain its legal ruling, harmonizing with the principles and objectives of Sharia. Utilizing a descriptive, analytical, and deductive approach, the research contends that the practice of electronic sex between spouses is inherently forbidden due to inherent dangers and ethical deviations that run counter to the essential goals of Sharia. Permission for such practices is only granted in cases of necessity and under requisite controls. Failure to adhere to these controls necessitates consideration of alternative solutions proposed in this research.